Skeletal muscle radio-density is an independent predictor of response and outcomes in follicular lymphoma treated with chemoimmunotherapy. - Michael P Chu (PLoS ONE, 2015)
Skeletal muscle radio-density (SMD) measures muscle radiation attenuation (in Hounsfield Units, HU) on computed tomography (CT) scans. Low SMD is prognostic of poor survival in melanoma, however its significance is unknown for hematologic malignancies. We performed a single institution, retrospective review of all follicular lymphoma (FL) patients who received chemoimmunotherapy from 2004-2009. Patient demographics, FL International Prognostic Index 1 (FLIPI-1), progression free (PFS) and overall survival (OS) were collected as primary endpoints. Objective response rates (ORR) were secondary. SMD was calculated using pre-treatment CT scans. In 145 patients reviewed, median values were age 59, FLIPI-1 of 2, stage III, and 8 chemoimmunotherapy cycles received. Median PFS for those with low SMD (<36.6 and <33.1 HU for patients with BMI ≤ 25 and > 25 kg/m2, respectively) compared to those with high SMD was profoundly worse, 69.6 vs. 106.7 months (hazard ratio [HR] 1.85; p = 0.01), respectively. Median OS was not reached in patients with high SMD vs. 92.7 months in low SMD patients (HR 4.02; p = 0.0002). Multivariate analysis supported lower SMD's OS detriment (HR = 3.40; p = 0.002) independent of FLIPI-1 (HR 1.46-2.76, p = 0.05) or gender. Low SMD predicted lower ORR, 83 vs. 96% (p = 0.01). SMD predicts survival independent of FLIPI-1 and potentially chemoimmunotherapy response. SMD is an inexpensive and powerful tool that can complement FLIPI-1.